Global mental health and trauma exposure: the current evidence for the relationship between traumatic experiences and spirit possession - Tobias Hecker; Lars Braitmayer; Marjolein van Duijl (European Journal of Psychotraumatology, 2015)
Background: We present a literature review on trauma exposure and spirit possession in low- and middle-income countries (LMICs). Despite the World Health Organization's objective of culturally appropriate mental health care in the Mental Health Action Plan 2013–2020, and the recommendations of the Inter-Agency Standing Committee to consider local idioms of distress and to collaborate with local resources, this topic still receives very little attention. Pathological spirit possession is commonly defined as involuntary, uncontrollable, and occurring outside of ritual settings. It is often associated with stigmatization, suffering, and dysfunctional behavior. While spirit possession has been discussed as an idiom of distress in anthropological literature, recent quantitative studies have presented support for a strong relationship between traumatic experiences and pathological possession states. Objective: The aim of this review was to investigate this relationship systematically in LMICs, in view of the debate on how to address the mental health gap in LMICs. Methods: Twenty-one articles, published in peer-reviewed English-language journals between 1994 and 2013, were identified and analyzed with regard to prevalence of possessive trance disorders, patients’ sociodemographic characteristics, and its relation to traumatic experiences. Results: The review and analysis of 917 patients with symptoms of possessive trance disorders from 14 LMICs indicated that it is a phenomenon occurring worldwide and with global relevance. This literature review suggests a strong relationship between trauma exposure and spirit possession with high prevalence rates found especially in postwar areas in African countries. Conclusions: More attention for possessive trance disorders in mental health and psychosocial intervention programs in humanitarian emergency settings as well as in societies in transition in LMICs is needed and justified by the results of this systematic literature review.